2016
DOI: 10.1002/jemt.22743
|View full text |Cite
|
Sign up to set email alerts
|

Label-free optical detection of age-related and diabetic oxidative damage in human aqueous humors

Abstract: In this study, we investigate the biochemical characteristics of oxidative stress in age-related macular degeneration (AMD) and diabetic retinopathy (DR) by analyzing aqueous humors. Nondiabetic cataract aqueous humor was used as the control. The level of oxidative damage was evaluated based on changes in Raman spectral intensity. Seven prominent peaks were detected at 1002, 1043, 1062, 1352, 1419, 1454, and 1656 cm . We proposed four multimodal biomarkers to distinguish these peaks based on the ratios of Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…An alternative approach is to use peak intensity ratios of each compound to identify each compound independently and quantify its concentration. This peak intensity ratio approach already has been reported and validated for ex vivo Raman investigation in human aqueous humor [33]. In a previous study, we developed a tailored MATLAB (Version 2017b, The Mathworks Inc., Natick, MA, United States) data processing program for in vitro and in vivo Raman detection of ocular drug topically delivered to the animal eyes [34,35] and demonstrated that with proper data processing, the molecular information can be extracted non-invasively from biological fluids in-situ and ex vivo.…”
Section: Discussionmentioning
confidence: 90%
“…An alternative approach is to use peak intensity ratios of each compound to identify each compound independently and quantify its concentration. This peak intensity ratio approach already has been reported and validated for ex vivo Raman investigation in human aqueous humor [33]. In a previous study, we developed a tailored MATLAB (Version 2017b, The Mathworks Inc., Natick, MA, United States) data processing program for in vitro and in vivo Raman detection of ocular drug topically delivered to the animal eyes [34,35] and demonstrated that with proper data processing, the molecular information can be extracted non-invasively from biological fluids in-situ and ex vivo.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to evaluating BG concentration, RS of AH can also be used to diagnose diabetes-related diseases. The biochemical characteristics of oxidative stress in age-related macular degeneration (AMD) and diabetes retinopathy (DR) using RS of AH were studied and the classification of AMD and DR using the spectral characteristics was achieved with a high sensitivity of 100% and high specificity of 100% ( Moon et al, 2016 ).…”
Section: Applications Of Raman Spectroscopy In Ocular Biofluid Detectionmentioning
confidence: 99%
“…Ex-vivo studies of enucleated human eyes have shown promise for development of ocular RS [387] , [390] [396] . The retina has a dense neuron structure and it is a highly metabolically active tissue [114] , [397] , which can be accessed externally through the optics system of the eye to perform RS.…”
Section: Raman Spectroscopy and The Eyementioning
confidence: 99%
“…Characteristic carotenoid peaks are present in both [422] . (d) Spectra taken of ex-vivo macular pigment tissue samples which were fixed using formalin fixative, using a 488 nm excitation wavelength [393] . (a) – (d) demonstrate that the same characteristic carotenoid peaks are present in in-vivo, fresh ex-vivo and fixed ex-vivo eye samples.…”
Section: Raman Spectroscopy and The Eyementioning
confidence: 99%